Infective Endocarditis in Northeastern Thailand - Watt, George (Centers for Disease Control and Prevention, 2014)
Despite rigorous diagnostic testing, the cause of infective endocarditis was identified for just 60 (45.5%) of 132 patients admitted to hospitals in Khon Kaen, Thailand, during January 2010–July 2012. Most pathogens identified were Viridans streptococci and zoonotic bacteria species, as found in other resource-limited countries where underlying rheumatic heart disease is common.